Bimbingan Pengembangan Belajar Bahasa Inggris Santri Kelas 3 KMI di Pondok Pesantren Modern Nurussalam - Zulaikah; Prasetio, Kiki Agung; Arif, Fatkul; Sifaurohmah, Ima (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Islamic boarding schools (Pesantren) are pivotal in Indonesian Islamic education, with a history spanning centuries and notable contributions to Indonesia's independence struggle. Amidst evolving challenges and stimuli from the Muslim reformist community, this study examines the educational approaches at Nurussalam Modern Islamic Boarding School. Key findings reveal that: 1) The conceptual framework for learning development at Nurussalam is primarily influenced by the ideologies of its caretakers. 2) The advancement of English language education is rooted in the belief that Muslims globally contribute to the dissemination of Islamic teachings. This study focuses on enhancing English language proficiency among third-grade KMI students at Nurussalam, employing the Direct Method and Question-and-Answer Technique. This educational development initiative is conducted by students from Nurul Huda University, emphasizing practical language skills crucial for global religious discourse.